Passivation of Transition Metal Dichalcogenides Monolayers with a Surface‐Confined Atomically Thick Sulfur Layer. Issue 4 (22nd March 2022) - Wang, Xiaojian; Feng, Qingliang; Xu, Shichen; Shang, Jing; Zhao, Yan; Wang, Shanshan; Zhou, Xi; Chen, Liling; Lei, Xingfeng; Li, Chun; Kou, Liangzhi; Zhang, Qiuyu; et al.
Abstract : Surface passivation can eliminate the charge doping of monolayer transition metal dichalcogenides (TMDs) during the device fabrication, which is important for the large‐scale production of ultra‐stable materials and high‐performance devices. The uniformity and atomical thickness of the passivating layers with a low dielectric constant (κ) are essentials to preserving the intrinsic properties of monolayer TMDs in harsh environments. Herein, a surface‐confined mechanism is developed to encapsulate TMDs monolayers by atomically thin sulfur layers with high spatial homogeneity (named S–MX2 ). The bottom bilayer S atoms are strongly confined by the upper S monolayers when the low‐κ S reaches three layers on the surface of TMDs, which spontaneously renders the uniform distribution on a large scale. The intrinsic electrical and optical properties of monolayer S–MX2 are well maintained and show excellent long‐term stability under harsh environments. Herein this work, a way to eliminate surface doping of monolayer TMDs for their practical application in large‐area‐integrated circuits is provided. Abstract : Herein, the surface‐confined effect of sulfur atoms on monolayer transition metal dichalcogenides (TMDs) is first explored, consequently facilitating the uniform distribution with sub‐nanometer thickness at solid–solid interface. TMDs monolayers are extremely passivated from kinds of surface‐doping agents, including polar solvent of acetone, H2 O, and alcohol, which also shows the advantage of photoetching‐free process for device fabrication.